Epidemiological characterization of incident cases of Rickettsia infection in rural areas of Urabá region, Colombia. - Juan Carlos Quintero Vélez; Daniel Camilo Aguirre-Acevedo; Juan David Rodas; Margarita Arboleda; Adriana Troyo; Francisco Vega Aguilar; Lisardo Osorio Quintero; Carlos Rojas Arbeláez (Public Library of Science (PLoS), 2018)
INTRODUCTION:Most of the studies related to rickettsial infection in Colombia are cross-sectional because of the challenge in conducting prospective studies on infectious disease that may have a difficult diagnosis. Although cross-sectional studies are essential to detect people exposed to rickettsiae, they are not suited to demonstrate the recent circulation of this pathogen in areas at risk of transmission. OBJECTIVE:To characterize the epidemiology of incident cases of Spotted fever group (SFG) rickettsial infection in humans and equines from rural areas of Urabá region in Colombia where outbreaks of rickettsiae previously occurred. MATERIALS AND METHODS:A prospective study was conducted in the Alto de Mulatos and Las Changas in the Urabá region. Serum samples and socio-ecological information were collected from 597 people enrolled in 2015, and a second sample was collected from 273 people a year later. Indirect immune-fluorescence assays for detection of IgG antibody against rickettsiae were done using slides with Rickettsia rickettsii antigens. A titer ≥128 was considered positive. Incident cases were defined as (i) serological conversion of IgG titers from seronegative to seropositive or (ii) at least a four-fold increase in IgG end point titers in the second sample. RESULTS:The cumulative incidence of rickettsial infection was 6.23% (95%CI 3.67-9.78) in humans and 32.31% (21/65) of incident cases in equines. Incident cases were mostly females (82.35%), the median age of cases was 41.02 years (IQR 18.62-54.1), and 29.41% reported tick bites during the study period. Results from multivariate analysis showed that removal of ticks after working outdoors is a protective factor for rickettsial infection (RR 0.26, 95%CI 0.08-0.84) and that a higher incidence of infection occurred in people who reported fever in the last year (RR 4.26, 95%CI 1.15-9.31). CONCLUSIONS:These results showed recent circulation of SFG rickettsiae in areas where previous lethal outbreaks have been reported, supporting the implementation of preventive measures to halt rickettsial transmission in the studied communities.